Literasi Digital dan Pola Berpikir Santri: Studi Fenomenologi di Pondok Pesantren Kalaga al-Kamal Denanyar Jombang - Ahmad Ahsan Akmal; Rohmat Hidayat (Lembaga Yasin AlSys, 2026)
Although digital literacy in Islamic education has received increasing attention, studies that specifically discuss the role of digital literacy in shaping the thinking patterns of santri in pesantren environments integrated with Islamic epistemological values remain limited. This study aims to analyze santri experiences in utilizing digital technology, describe their thinking patterns in evaluating and using digital information, and identify factors that influence digital literacy in the pesantren environment. This study used a qualitative approach with a phenomenological design, involving 26 santri, one caregiver, and two administrators of Pondok Pesantren Kalaga Al-Kamal Denanyar Jombang, who were selected purposively. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation as well as member checking. The results showed that santri digital literacy developed in a controlled situation through technology-use rules, time restrictions, and intensive mentoring. The thinking patterns of santri tended to be selective and cautious in evaluating digital information, influenced by pesantren policies, the roles of caregivers and administrators, and the individual awareness of santri grounded in Islamic Religious Education values. The novelty of this study lies in the integration of Islamic principles, namely iqra’, tabayyun, and tafakur, as an analytical framework for digital literacy that strengthens Social Constructivism theory in the context of Islamic education. The conclusion of this study affirms that institutional mentoring plays an important role in shaping santri as responsible digital citizens. The implications of this study provide theoretical contributions to the development of digital literacy based on Islamic epistemology and practical contributions for pesantren in formalizing a digital literacy curriculum based on Islamic values.